Pengaruh Motivasi Kerja Islam dan Budaya Kerja Islam Terhadap Produktifitas Kerja karyawan BMT di GERBANGKERTASUSILA - Achmad Nur Iman; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study attempts to know the importance of perception employees of islamic woek motivation and islamic work culture to labor islamic productivity whether partial and simultaneous on the quality of performance bmt areas gerbangkertasusila east java. A population that used is all the employees bmt taken by random or shuffle as many as 200 respondents.Technique the analysis used is linear regression multiple. The research results show that simultaneously being tested use test F shows that there has been significant impact between variable freely with variable bound.While in partial being tested use test t indicate the presence of some variable free namely motivation work islam and culture islamic work to labor productivity islamic bmt some have had a positive impact significant and some influential negative to productivity performance office bmt areas gerbangkertasusila east java.Keywords: Baitul mal wat tamwil, Islamic work motivation, Islamic work culture, employees’ productivityREFERENCES Departemen Agama RI,  Al-Quran Terjemah (Jakarta : CV Darus Sunnah,2002)Afzalurahman, Muhammad Sebagai Seorang Pedagang, (Jakarta : Yayasan Swarna Bhumy, 1997)Alma, Buchari dan Donni Juni Priansa, S.Pd, manajemen bisnis syari’ah, Bamdung: Alfabeta, 2009.Cahyono, Bambang Tri, Manajemen Sumber Daya Manusia, Jakarta: Badan Penerbit IPWI, 1996. Creswell, John W., 2003, Research Design ; Qualitative, Quantitative, And Mixed Methods Approaches, Second Edition, Sage Publications, Inc., New Delhi, India. Darwan Rahardjo, Muhamad Islam dan Transformasi Sosial-Ekonomi, Yogyakarta: LSAF, 1999.Djazuli, Ahmad, 2002. Implementasi Kemaslahatan Umat dalam Rambu Rambu. Didin Hafidhuddin dan Hendri Tanjung, Manajemen Syariah dalam Praktik, (Jakarta : Gema Insani Press, 2003).Ghozali, Imam, 2005, Aplikasi Analisis Multivariate dengan Program SPSS, Badan Penerbit Universitas Diponegoro, Semarang.Hasibuan, Malayu S.P., 1996, Manajemen Dasar, Pengertian dan Masalah, Edisi Kedua, Jakarta: PT Toko Gunung Agung. Karim, Adi Warman, Ekonomi Islam, Jakarta: Gema Insani Press,2001Mursi,Abdul Hamid, 1997. SDM yang Produktif Pendekatan Al-Quran dan Sains, Jakarta : Gema Insani Press 1997.Muhammad Ismail Yusanto dan Muhammad Karebet Widjajakusuma, Menggagas Bisnis Islami, (Jakarta : Gema Insani Press, 2002).Munir Sukoco, Badri, Manajemen Administrasi Perkantoran Modern. Surabaya: Erlangga, 2007.Qardhawi, Yusuf, Norma dan Etika Ekonomi Islam, Jakarta:Gema Insani Press, 1997. Rdliyah, Ummi, Pendekatan Postmoderns Dalam Penelitian Ilmu Sosial Dan Budaya, Tidak DipublikasikanSujudi Ragil Putra, Pengaruh Motivasi Kerja, Lingkungan Kerja dan Pengawasan Kerja Terhadap Produktivitas Kerja Karyawan Pada BMT BinaI hsanul Fitri Yogyakarta, Skripsi, Prodi Ekonomi UII Yogyakarta, 2006Syafii Antonio, Muhamad dan Tim Tazkia,  Ensiklopedia Leadership & Manajemen Muhammad SAW “The Super Leader Super Manager” buku 2, Bisnis dan Kewirausahaan, (Jakarta : Tazkia Publishing, 2012)Triguna, 1995, Budaya Kerja, Jakarta: Gunung Agung, 1995.Tasmara, Toto,2002, membudayakan etos kerja Islami, Jakarta: gema insani press, 2002. Sugiyono, 1999, Statistika Untuk Penelitian, Cetakan Kedua, CV Alfabeta, BandungSaleh, Akh. Muwafik. 2009. Bekerja dengan Hati Nurani. Jakarta: Erlangga.Sugiyono, 2009, Metode Penelitian Kuantitatif, Kualitatif dan R&D, Bandung : Alfabeta.Sinungan, Muchdarsyah. (2003). Produktivitas apa dan Bagaimana. Jakarta: Bumi Aksara. Umar, Husein ”Studi Kelayakan Bisnis”, PT. Gramedia Pustaka Utama, Jakarta, 1997.Umar, Husein, 2004, Metode Penelitian Untuk Skripsi Dan Tesis Bisnis, Cetakan Keempat, PT. Raja Grafindo Persada, Jakarta Ghozali, Imam, 2005, Aplikasi Analisis Multivariate dengan Program SPSS, Badan Penerbit Universitas Diponegoro, Semarang.